Geomorphologische Forschungen im südwestafrikanischen Kaokoveld zum angeblichen vollariden quartären Kernraum der Namibwüste - Rust, Uwe (ERDKUNDE, 1987)
According to the present state of research, there exists a central area in the Namib desert between ca. 23°-15°s. latitude, which has not been affected by Quaternary climatic changes (fig. 2). This conception was checked in the field by means of geomorphological methods. The results are as follows: for the area between 23° and 18° s. latitude, the above conception has to be discarded as false. The remaining core (fig.14) (between 18° and 15 s. latitude) seems to be only the regional expression of a lack of know ledge. Fluvial terraces and sediments testify that the northern Namib has even repeatedly been affected by Quaternary climatic changes (fig.12). Along the Hoanib and the Hoarusib rivers, climatic oscillations in a time scale of 102a are evident. The coastal upwelling along the northern Namib during the last glacial period was less intensive than today. Fluvial terraces in well-defined geomorphological situations are useful palaeoenvironmental indicators in the desert.